Analysis of Factors Affecting the Financial Performance in Cooperatives (Study at KPRI Universitas Brawijaya) - Lestari, Elly; Hidayat, Imam; Askiyanto, Moh; Setyawati, Yuni; Ikis, Letriana (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Financial â€œperformance plays an important role in knowing and assessing financial performance income so that cooperatives can make the right decisions in business development. The purpose of this study was to determine the factors that influence income on financial performance at the Malang Brawijaya Cooperative. The research conducted is research using quantitative methods. The data used is secondary data in the form of financial reports of the Malang Brawijaya Cooperative starting from 2018-2021. The data analysis method is financial ratio analysis. The results of the study prove that the factors that influence the financial performance of the Malang Brawijaya Cooperative, namely the liquidity ratio and leverage ratio, are stated to be healthy because cooperatives have high asset and capital values to pay business obligations, while the activity ratio factor and profitability ratio are declared to be very unhealthy because business activity is low and has low operating profit. Based on the these results, the cooperative of the university is suggested to calculate financial ratios inâ€ financial decision-making.